A phosphorescent copper(i) coordination polymer with sodium 3, 5-dimethyl-4-sulfonate pyrazolate. Issue 40 (2nd October 2017) - Attilio Ardizzoia, G.; Brenna, Stefano; Civati, Francesco; Colombo, Valentina; Sironi, Angelo
Abstract : A phosphorescent copper(i ) coordination polymer has been synthesized and characterized via ab initio PXRD. Abstract : A phosphorescent copper(i ) coordination polymer with the sodium salt of 3, 5-dimethyl-4-sulfonate pyrazole (HL Na ) has been prepared and structurally characterized. The presence of the SO3 Na substituent in position 4 of the pyrazole ring led to a 3D polymeric species in which an organic/inorganic/organic sandwich motif is observed and repeated along the a axis through zig-zag chains of linear coordinated Cu(i ) ions. The inorganic core of the sandwich consists of a trapezoidal grid of Na-ions interconnected by μ-(κO;κ 2 -O ′, O ′′ )-bridging sulfonates and bridging water molecules; H-bonds can be also found between water molecules and SO3 − groups. In the solid state, the copper derivative showed an interesting phosphorescent behavior when irradiated with UV light, with a yellow emission (570 nm) and a good absolute quantum yield ( Φ PL = 0.44), together with a remarkable Stokes shift of 2.50 eV.